REPRODUCTIVE BIOLOGY OF THE BLUE SPOT MULLET VALAMUGIL SEHELI (FORSKAL) FROM MANGALORE REGION, SOUTHWEST COAST OF INDIA - Moorthy, K. S. Venkatesha; Reddy, H. R. V.; Annappaswamy, T. S. (Journal of Indian Fisheries Association, 2015)
The blue spot mullet Valamugil seheli spawns once a year between August and February with peak spawning during OctoberÂ· November. Males attain maturity at 250.5 mm and females at 256.5 mm total length. Males outnumbered females in the commercial catches, although the sex-ratio (M: F = 1:0.90) in the population showed no significant deviation. The fecundity of this species varied from 108378 to 910350 eggs with an average of 327944. Linear relationships were found between fish length, gonad weight and fecundity; and between fish length, fish weight and ovary weight. Keywords : spawning size at first maturity, sex ratio, fecundity